Synthesis, characterization and biological activity of 3-(1-cyclohexyl)azetidinyl methacrylate monomer and its homopolymer - Coskun, M; Erten, H; Demirelli, K; Dilsiz, N; Ahmedzade, M (John Wiley & Sons Ltd, 2000)
3-(1-Cyclohexyl)azetidiniyl methacrylate (CyAMA), a new methacrylate monomer, was synthesized by reaction of the sodium salt of 1-cyclohexylazetidin-3-ol with methacryloyl chloride. The monomer was polymerized at 60 degrees C in 1,4-dioxane solution using 2,2'-azobisisobutyronitrile (AIBN) as an initiator. CyAMA and poly(CyAMA) were characterized by FTIR and H-1 and (CNMR)-C-13 spectroscopy. The activation energy of the initiation step of the polymerization was estimated from initial rates, and the number average molecular weight of the homopolymer was determined by gel permeation chromatography (GPC). The antibacterial and antifungal effects of the monomer and homopolymer were investigated on various bacteria and fungi. The thermal stability of poly(CyAMA) was investigated by TGA, and its glass transition temperature was determined by DSC as 93 degrees C. (C) 2000 Society of Chemical Industry.
Keywords: synthesis; characterization; azetidinyl methacrylate; antibacterial and antifungal effects